PENGEMBANGAN STRATEGI BISNIS PADA HOTEL XYZ DENGAN ANALISIS MATRIX IFE DAN EFE - Anjani, Dian Pramudhita; Sari, Intan Pramitha; Hermawaty, Nadia; Yasa, Ni Nyoman Kerti; Giantari, I Gst Ayu Ketut (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2024)
The increases of tourist visits in Bali can influence the development of the hotel industry. The significant increase in the number of tourists has caused demand for accommodation services, especially hotels, which has an impact on increasing hotel competition. This research aims to identify and design a business strategy at hotel XYZ through several stages such as IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) analysis. This research uses a qualitative descriptive method with data collection methods through interviews. Based on the EFAS and IFAS values, the company is in quadrant V with a hold and maintain business strategy. The results of this research provide strategies that can be implemented by XYZ Hotel, namely market penetration strategies and product development strategies.